BETTER SENTENCE BUILDING SKILLS THROUGH COLLOCATIONS: A WAY TO NATURALIZATION OF ENGLISH SPEECH - Moehamad Ridhwan; Welly Ardiansyah; Koryati - (Politeknik Negeri Sriwijaya, 2017)
A language requires some certain ways of putting their words together to get some ideas across. These words have some relationship and bond that may escape the attentions of some EFL learners who rely merely upon grammatical skills and vocabulary to build sentences. It is true that grammatical structure connects all the words together to convey the meaning, but there is more to it than meet the eyes when ‘naturalness’ is also our concern. At times, the influence of one’s mother tongue over one’s diction in a foreign language is responsible for the production of unnatural expressions in that foreign language. Once this problem comes to surface, a better look at word pairing-habit in that foreign language should be a priority in which case collocations are the stars on the stage, worthy of our most attention.